Outbreak of fescue foot in a livestock in Salta, Argentina (FAVE Sección Ciencias Veterinarias, 2018)
Festuca arundinacea is a perennial grass which use as forage is widespread worldwide. This report describes a “fescue foot” outbreak in the Northwest of Argentina. Beef cattle herd were affected and the incidence was 5%. The clinical signs were claudication, edema in the limbs, gangrene in the extremities and exungulation. The grazing areas where the animals remained corresponded to a natural batch of fescue. Neotyphodium coenophialum infestation level was 71%. The clinical presentation of fescue root is well described but barely reported in Argentina. In the outbreak presented here diagnosis was confirmed by the clinical and epidemiological antecedents as well as the high level of infestation of the pasture. The toxicity of fescue is a worldwide distributed problem. In Argentina, the disease is well known in the central region of the country. Scarce information is available regarding the toxicity of this species for northwestern Argentina.